Swine vesicular disease. Serological survey by double immunodiffusion assay - ΔΗΜΗΤΡΙΑΔΗΣ, Ι.; ΠΑΠΠΟΥΣ, Χ.; ΖΑΦΕΙΡΙΟΥ, Γ.; ΧΑΤΖΗΣ, Θ.; ΓΕΩΡΓΑΚΟΠΟΥΛΟΣ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
214 sera of 18 herds from the outbreak area and its vicinity were tested by double immunodiffusion (DID) in agarose gel. 66 sera of 4 herds from the outbreak area were positive in percentages 96-100% by sample. The precipitating antibody titer oscilled 1:2 to 1:32. The results were identical with those obtained by serum-neutralisation test, so the DID test has the same sensitivity with the latter